PEMBERDAYAAN MASYARAKAT DALAM BIDANG KESEHATAN PENDIDIKAN DAN PERTANIAN DI DESA KEPALA SUNGAI KECAMATAN SECANGGANG KABUPATEN LANGKAT - Nudia Yultisa; Rahmi Dwi Handayani Rambe; Syamsafitri Syamsafitri; Tubagus Hutriadi (Jurnal Pengabdian Mitra Masyarakat, 2023)
The village of the head of the river is one of the villages in the Secanggang District, Langkat Regency. Dominant residents work as farmers and self-employed. The main activities of the Thematic Community Service Program carried out by students are cleaning drainage, teaching elementary school children in class, teaching children the Koran and tutoring at home, counseling on organic fertilizer and others that are effective for a month. Based on an initial survey to several hamlets that the main problems are the dirty living environment of the community, clogged drainage channels, puddles of water, there are still school children who cannot read and count along with the moral and ethical decadence of school children and the low knowledge of residents/farmers about fertilizers. organic. The implementation of the activities is carried out by data collection methods and implementation methods where the student activities above are accompanied by DPL lecturers to help the community. The results of the Thematic KKN activities for one full month consisting of cleaning drainage channels, holding class lessons and recitations at home and holding counseling on subsidized and non-subsidized organic fertilizers have been well implemented. There are no obstacles and challenges in the activity because it is carried out in mutual cooperation, namely jointly between students and the community. Hopefully, the Thematic Community Service Program can benefit the community and also for students as an experience of living in a community, able to develop and apply academic knowledge according to their respective fields.